2015
DOI: 10.3390/s150717621
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Layer Service Discovery Mechanism for OLSRv2 Mobile Ad Hoc Networks

Abstract: Service discovery plays an important role in mobile ad hoc networks (MANETs). The lack of central infrastructure, limited resources and high mobility make service discovery a challenging issue for this kind of network. This article proposes a new service discovery mechanism for discovering and advertising services integrated into the Optimized Link State Routing Protocol Version 2 (OLSRv2). In previous studies, we demonstrated the validity of a similar service discovery mechanism integrated into the previous v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Authors in [10,11] have discussed the concept of using DSR and TORA routing protocols for network service discovery. While others considered Proactive and hybrid routing protocols have also been extended to support SD such as OLSR and ZRP [12][13][14].…”
Section: Sd In Manet Contextmentioning
confidence: 99%
“…Authors in [10,11] have discussed the concept of using DSR and TORA routing protocols for network service discovery. While others considered Proactive and hybrid routing protocols have also been extended to support SD such as OLSR and ZRP [12][13][14].…”
Section: Sd In Manet Contextmentioning
confidence: 99%
“…Chanei and Charoenpanyasak 3 utilized the cross‐layering technique to develop a modified AODV routing method for wireless sensor networks with decreased control traffic overhead and reduced energy consumption. Service discovery and path establishment protocol for proactive and reactive ad hoc networks is analyzed and compared in Vara and Campo 4 . Specifically, it employed the Optimized Link State Routing Protocol Version 2 (OLSRv2) and AODV routing protocols in dense networks with high‐speed nodes.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Furthermore, cross‐layer designed to eliminates repetitive functions in neighbor layers, and in order to improve the overall performance of the network, the interconnectivity between stack layers is exploited. Recent studies have shown that integrated cross‐layers improve network performance in terms of energy efficiency 22 . But our literature is limited to investigate various service redundancy phenomena problems and discuss different cluster‐based routing protocols methods proposed in order to solve those problems in wireless sensor and mobile ad hoc networks.…”
Section: The Basic Concepts Of Service Discover and Clustering Approachmentioning
confidence: 99%
“…From the pool of proposed models, a modern service discovery method is presented 22 for detecting services joined into OLSRv2. Service discovery message (SDM) is a modern type‐length‐value structure (TLV) integrated with OLSRv2 protocol aiming to advertise services 68,69 .…”
Section: Service Discovery and Cluster‐based Routing Protocolsmentioning
confidence: 99%